The FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA PADA KARYAWAN CV. WORKSHOP CHAMPION LEST DI KOTA AMBARAWA - Angieska, Princesa (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of Selection and Competence on Employee Productivity at CV. Champion Lest Workshop in Ambarawa city. This study uses a quantitative research method. The population used in this study are all employees who work at CV. Lest Champion Workshop in Ambarawa city in 2023. The sample used in this research was Saturated Sampling which is included in Non Probability Sampling, which means that all members of the population were sampled, namely 103 employees. Analysis of research data using SPSS For Windows software version 24. The results of this research show that there is a Selection (X1) has a positive and significant effect on Employee Work Productivity (Y), partially the t count is 2.091 and the significance value is 0.039 with an increase in Selection which can influence the Employee Work Productivity variable by 21.8%. Competence (X2) has a positive and significant effect on Employee Productivity (Y) partially t count 5.287 and a significance value of 0.000 with an increase in Competence can affect the Employee Productivity variable by 42.3%. The test results for the Coefficient of Determination (R2) obtained an Adjusted R Square value of 0.519 or 51.9%, indicating that the Employee Productivity variable is influenced by the Selection and Competence variables while the remaining 0.481 or 48.1% is influenced by other variables which is not in this study.